The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2016
DOI: 10.3168/jds.2015-10465
|View full text |Cite
|
Sign up to set email alerts
|

Lactoferrin affects the adherence and invasion of Streptococcus dysgalactiae ssp. dysgalactiae in mammary epithelial cells

Abstract: Streptococcus dysgalactiae spp. dysgalactiae is an important causative agent of bovine mastitis worldwide. Lactoferrin is an innate immune protein that is associated with many functions including immunomodulatory, antiproliferative and antimicrobial properties. This study aimed to investigate the interactions between lactoferrin and a clinical bovine mastitis isolate, S. dysgalactiae spp. dysgalactiae DPC5345. Initially a deliberate in vivo bovine intramammary challenge was performed with S. dysgalactiae DPC53… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 47 publications
0
8
0
Order By: Relevance
“…The protein has antimicrobial properties as it binds iron, which is essential for bacterial and viral replication [ 42 ]. Since iron demand of streptococcal species is rather low, lactoferrin was demonstrated to have a bacteriostatic effect on different streptococci [ 43 ]. Clinical trials attempted on seven Holstein Friesian cows showed that 67% of the mammary quarters infected with S. uberis wild-type showed clinical manifestations of mastitis (clots in produced milk, firm and moderate swelling of the mammary glands with red coloration).…”
Section: Pathogenesis and Virulence Factorsmentioning
confidence: 99%
See 1 more Smart Citation
“…The protein has antimicrobial properties as it binds iron, which is essential for bacterial and viral replication [ 42 ]. Since iron demand of streptococcal species is rather low, lactoferrin was demonstrated to have a bacteriostatic effect on different streptococci [ 43 ]. Clinical trials attempted on seven Holstein Friesian cows showed that 67% of the mammary quarters infected with S. uberis wild-type showed clinical manifestations of mastitis (clots in produced milk, firm and moderate swelling of the mammary glands with red coloration).…”
Section: Pathogenesis and Virulence Factorsmentioning
confidence: 99%
“…After 8 h of exposure to lactoferrin, a dose-dependent growth inhibition of S. dysgalactiae was observed in a previous study due to the antimicrobial properties of the protein. In addition, assays conducted with HC-11 murine epithelial cells revealed lactoferrin-dependent decrease of bacterial adhesion [ 43 ]. Lactoferrin may serve as a bridging molecule for S. uberis , consequently promoting adherence and internalization into mammary epithelial cells, thereby surviving host defense mechanisms by immune evasion [ 46 ].…”
Section: Pathogenesis and Virulence Factorsmentioning
confidence: 99%
“…Bacteriocins such as nisin A have demonstrated antibacterial activity against mastitis pathogens ( Malvisi et al, 2016 ). Immune stimulants such as ginseng ( Beccaria et al, 2018 ) and the use of plant-derived compounds ( Maia et al, 2018 ) and immune proteins such as lactoferrin ( O’Halloran et al, 2016 ) have also been tested in this regard. Probiotic lactic acid bacteria (LAB) strains have been reported to eliminate mastitis-causing staphylococcal biofilms ( Wallis et al, 2019 ).…”
Section: Introductionmentioning
confidence: 99%
“…Streptococcus is a bacterium that is often found in mastitis, including S. agalactiae, S. dysgalactiae, and S. uberis [4,5]. One of the virulence factors in streptococcus is a lactoferrin-binding protein (LBP), but there are differences among these organisms, especially the pathogenesis of milk lactoferrin protein to interact with streptococcus [6]. Lactoferrin is a host innate immune protein that acts as antibacterial, immunomodulator, antiadhesion, and has iron-binding properties [7,8,9].…”
Section: Introductionmentioning
confidence: 99%